2022
DOI: 10.1002/er.8260
|View full text |Cite
|
Sign up to set email alerts
|

Design and numerical simulation of highly efficient mixed‐organic cation mixed‐metal cation perovskite solar cells

Abstract: Summary Mixed cation perovskite type materials have recently shown considerable potential in high‐efficiency single‐ and multi‐junction solar cell devices. However, the operating principles of multiple cation‐based perovskite solar cells are currently poorly understood. Furthermore, the photovoltaic performances of mixed cations‐based perovskites solar cells are investigated using device simulator program. Inorganic TiO2 and Cu2O were used as electron transport layer and hole transport layer, respectively, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…We conclude that the relationship between the band gap and dielectric constant is an inverse relationship. The increase in the value of the dielectric constant corresponds to the decrease in the value of the band gap [ 21 , 22 , 23 , 24 , 25 ]. In fact, in a high-symmetry structure such as cubic, the electronic charge distribution is very uniform, leading to weak polarization effects and a low dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…We conclude that the relationship between the band gap and dielectric constant is an inverse relationship. The increase in the value of the dielectric constant corresponds to the decrease in the value of the band gap [ 21 , 22 , 23 , 24 , 25 ]. In fact, in a high-symmetry structure such as cubic, the electronic charge distribution is very uniform, leading to weak polarization effects and a low dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…However, theoretical studies have shown that if the stability issues are overcome, the Ge-PSC can achieve PCE beyond 20%. Kanoun et al 32 explored MAGeI 3 through numerical modeling and attained the PCE of 21.6%. In another study, Singh et al 33 also focused on Ge based cells modelling, achieving an outstanding PCE of 26.3%.…”
Section: Introductionmentioning
confidence: 99%